DESIGN AND ANALYSIS OF LIGHTNING PROTECTION FOR SUBSTATIONS - Malik, U. F.; Izhar, T.; Saleem, Y.; Arshad, M. J. (The Nucleus, 2014)
The study of natural disturbance lighting and protection against is very important in protection of substation. For designing and analysis of lightning protection of substations, a computer program has been developed with the help of Matlab in graphical user interface (GUI). Shield wire scheme has been implemented for lightning protection. Economical criterion has been given the major preference in this computer application while maintaining the protection. This computer application Matlab tool can quickly design lightning protection for Substation and it may prove to be very helpful for design engineers in the field. In this paper methodology and inputs/outputs of the developed program tool is presented. This study also shows an example of local Rohri substation with results and developed program tool proved to be useful as discussed in conclusion.